DAMAGE PARAMETERS IDENTIFICATION OF ALUMINUM ALLOY BASED ON ANISOTROPIC GTN MODEL - XIAO Jin; HU YuMei; JIN Xiaoqing; CHEN Minzhi; ZHOU YingE; SHAO JinHua (Jixie qiangdu)
In this paper,the GTN damage model coupled with anisotropic yield criteria were implemented by establishing a user defined subroutine under the framework of LS-DYNA/Explicit finite element code. Taking 6016 aluminum alloy as the research object,the GTN damage parameters were identified by comparing the numerical and experimental tensile results. Using traditional inverse calibration method of regarding the force versus displacement curve as the only judgment criteria,a group of GTN parameters was determined,and also take into account of the fracture and the necking behavior,another group of GTN parameters was determined. Then the two groups of GTN parameters were applied to the tensile process simulation of 6016 aluminum alloy in turn. The results showed that the first group of GTN parameter cannot accurately reflect the actual fracture and the necking behavior,while using the second group of GTN parameters,the simulation results are in good agreement with the experimental results.